2006
DOI: 10.1523/jneurosci.3651-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Layer Positioning of Late-Born Cortical Interneurons Is Dependent on Reelin But Not p35 Signaling

Abstract: We tested the response of interneurons to the absence of Reelin signaling or p35 in the mouse neocortex. We provide three independent strands of evidence to demonstrate that layering of late-born (but not early-born) interneurons is regulated by Reelin signaling. First, early-born and late-born interneurons behaved differently in mice lacking Reelin or disabled 1 (Dab1). Early-born interneurons showed layer inversion, whereas late-born interneurons did not demonstrate layer inversion but were randomly distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 50 publications
0
45
2
Order By: Relevance
“…These results suggest that the distribution of projection neurons and/or a normal radial glia organization is required for interneurons to distribute appropriately in the cortex. These findings challenge recent experiments in which wild-type interneurons were found to distribute normally when transplanted into the lateral ventricle of Dab1 mutant embryos (Hammond et al, 2006). Other than the obvious methodological differences that exist between both experiments (transplantation in the MGE versus transplantation in the lateral ventricle), we cannot explain the origin of this discrepancy.…”
Section: Layer Acquisition By Cortical Interneurons Does Not Directlycontrasting
confidence: 93%
“…These results suggest that the distribution of projection neurons and/or a normal radial glia organization is required for interneurons to distribute appropriately in the cortex. These findings challenge recent experiments in which wild-type interneurons were found to distribute normally when transplanted into the lateral ventricle of Dab1 mutant embryos (Hammond et al, 2006). Other than the obvious methodological differences that exist between both experiments (transplantation in the MGE versus transplantation in the lateral ventricle), we cannot explain the origin of this discrepancy.…”
Section: Layer Acquisition By Cortical Interneurons Does Not Directlycontrasting
confidence: 93%
“…Previous studies have suggested differences between the migratory properties of murine MGE cells born at different developmental stages (29)(30)(31). Because chicken E6.5, the time when the donor MGE cells were dissected out, is in the middle of the neurogenic period in the chicken dorsal telencephalon (E5-8) (32), chicken MGE cells born earlier or later than E6.5 may behave differently from E6.5 chicken MGE cells.…”
Section: Resultsmentioning
confidence: 99%
“…None of the differentially expressed genes were previously shown to play a specific role in SST interneuron differentiation, though a number of them play a role in interneuron migration or differentiation in general. Disabled-1 (DAB1), has been implicated in interneuron migration, though it may not be required for this process (Hammond et al, 2006;Pla et al, 2006). Deletion of contactin-associated proteinlike 2 (CNTNAP2) disrupts interneuron migration, results in a loss of interneurons, and mutations in CNTNAP2 are associated with epilepsy and autism in humans (Penagarikano et al, 2011).…”
Section: Discussionmentioning
confidence: 99%